Digital Image Processing Approach for Determination of Leaf Area of Field Crops - Santra, Priyabrata; Mansuri, Shekh Mukthar; Dhaka, Bajrang Lal; Mahla, Hans Raj (Annals of Arid Zone, 2021)
A digital image processing method has been developed to estimate the leaf area of clusterbean using commonly available printer-cum-scanner in a desktop computer. In this method, leaves were collected from the field and scanned in the laboratory over a transparent sheet placed on the top glass cover of the scanner bed. Further, the scanned image was processed through a programing code to compute the leaf area. A comparison of digital method with grid method revealed that the leaf area was slightly lower in grid method than in digital method because in the digital method minute details of leaf area could be accommodated whereas in grid method it was not. The digital method could be more suitable for crops with small leaves where the grid method is tedious. In future, smart phone based android application may be developed to capture the photographs of the leaves in the field and analysed subsequently to obtain the area. The quick assessment of leaf area using digital method may aid in timely management of water and nutrients in the field.Key words: Leaf area index, digital image processing, grid method, clusterbean.